PENGEMBANGAN E-MODUL INTERAKTIF BERBASIS HYPERLINK UNTUK MENINGKATKAN KETERAMPILAN KOMUNIKASI INFORMAL BAHASA INGGRIS DI SMP MUHAMMADIYAH CIPANAS - Fenty Erdiyanti; Dirgantara Wicaksono (Media Riset Bisnis Manajemen Akuntansi, 2025)
This research aims to develop an interactive e-module based on hyperlinks to improve informal English communication skills among seventh-grade students at SMP Muhammadiyah Cipanas. The background of this study highlights the limitations of conventional English learning methods that rely heavily on textbooks and lack interactive digital support, particularly in informal communication contexts. Using the 4D development model (Define, Design, Develop, Disseminate), this study employed a research and development approach with both qualitative and quantitative methods. Data were collected through expert validation, student questionnaires, and pre-test and post-test assessments. The e-module was designed using a hyperlink-based structure that includes multimedia elements such as videos, audio, and animated content to support self-paced learning. The results of the study indicate that the e-module is valid and feasible based on expert judgment and is effective in improving students’ vocabulary and speaking abilities in informal settings. Furthermore, student responses showed positive engagement and motivation while using the e-module. This research concludes that hyperlink-based interactive e-modules are a viable innovation to support student-centered and context-based English learning in junior high schools. Keywords : communication skills, e-module, hyperlink, informal English, interactive media.